HEATHCLIFF’S SELF ACTUALIZATION IN WUTHERING HEIGHTS BY EMILY BRONTE - Ririn Fatmawati (Universitas Sebelas Maret, 2020)
This study discusses Heathcliff’s Self-Actualization in Wuthering Heights written by Emily Bronte which is set in the Yorkshire moors of Northern England. The inductive method is used to briefly discuss the topic. It means that the analysis starts from the specific concept goes to general conclusion. The data used in this article are techincally collected by library research. This study applies Maslow’s Hierarchical Theory of motivation. There are five hierarchies of needs which have to be fulfilled before someone goes through to accomplish self actualization, those are physiological needs, safety needs, belongingness and love needs and the last needs are self-esteem needs. This study focuses on how Heathcliff fulfil his psychological need, how he get his safety need, how he get the belongingness and love need, how he reach his self-actualization. The study seeks to find Heathcliff’s success in Wuthering Heights in achieving his self-actualization. Heathcliff would achieve his self-actualization as he needs to become a total type of person to fulfill his goal whatever he has accomplished. He could unify Wuthering Heights and Thrushcross Grange, and turn Hareton into a slave.